2009 Fourth International Conference on Internet and Web Applications and Services 2009
DOI: 10.1109/iciw.2009.16
|View full text |Cite
|
Sign up to set email alerts
|

Paircoding: Improving File Sharing Using Sparse Network Codes

Abstract: BitTorrent and Practical Network Coding are efficient methods for sharing files in a peer-to-peer network. Both face the problem to distribute a given file using peers with different and dynamic bandwidth and only temporal availability. For this, BitTorrent partitions the files and uses the upload and download of each peer. In addition to this, Practical Network Coding uses a random linear combination of the parts. The original file can be decoded by a matrix operation as soon as enough linear combinations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…To avoid this problem, our C4 utilizes sparse RLNC proposed in [28] to control overhead. Given k original data packets as one generation, sparse RLNC first randomly chooses p data packets, then performs RLNC on these p packets to generate a coded packet.…”
Section: Implementation Details Of Our C4mentioning
confidence: 99%
“…To avoid this problem, our C4 utilizes sparse RLNC proposed in [28] to control overhead. Given k original data packets as one generation, sparse RLNC first randomly chooses p data packets, then performs RLNC on these p packets to generate a coded packet.…”
Section: Implementation Details Of Our C4mentioning
confidence: 99%
“…Then, any two peers with progress 1 2 can decode the file and thus have full availability of the file. Using this technique we have proved in [10] the following theorem for the scenario depicted in Figure 3. …”
Section: Paircodingmentioning
confidence: 99%
“…We have presented Paircoding [10] as a sparse form of Network Coding. Here, each code block is a linear combination of at most two original blocks.…”
Section: Paircodingmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11] we have introduced Pair Coding. We have shown that it performs at least as good as BitTorrent with a constant factor increase in complexity.…”
Section: Previous Workmentioning
confidence: 99%